The Effect of Work Discipline on Performance Employee on Pt. Company Plantation London Sumatra Indonesia Tbk - Ary Risaldi. N Ary Risaldi. N; Hasnawi Haris; Andi Aslinda (Public Resource Innovation Management and Excellence, 2025)
The era of globalization is marked by the rapid development of everythingactivity business. Change environment such dynamic has force various types of companies to carry out the vision, mission and adaptation strategies in company structure, culture and system. Study This aim For know How descriptionDiscipline Work on Employees of PT. PP LONSUM INDONESIA TBK. picture picture performance employee on Employee PT. pp LONSUM INDONESIATBK., And how big the influence of Work Discipline on Employee Performance at PT. pp LONSUM INDONESIA TBK. Study This is study quantitative with the number of respondents as many as 82 people using the approach descriptive.Collection data done with technique observation, questionnaire, Anddocumentation. Technique analysis data Which used that is test validity For test the questionnaire, descriptive analysis using the frequency distribution,percentage, flat – flat ( mean ) And standard deviation, regression simple For test the hypothesis and product moment correlation test to test whether there issignificant relationship and how much influence Work Discipline has onPerformance Employee on PT. pp LONSUM INDONESIA TBK. The results of this study indicate that: (1) Work Discipline of PT. ppLONSUM INDONESIA TBK. is at on category Good reviewed from aspectpresence, obedience on regulation Work, obedience on standard Work, levelvigilance tall and work ethically. (2) Employee Performance PT. pp LONSUMINDONESIA TBK. are in the good category in terms of the aspect of work quality, quantity of work, responsibility, initiative, cooperation and obedience. (3) As big as 0.583 influence Discipline Work to performance Employee PT. ppLONSUM INDONESIA TBK. moderately strong correlation.